Unusual rib tumor: Parosteal lipoma with extensive osteochondromatous metaplasia - Sathe Pragati; Vaideeswar P (Wolters Kluwer Medknow Publications, 2008)
Lipomas of the bone usually occur in the long bones and are seen in the fifth to seventh decade of life. Rib lipomas are rare and those having parosteal location are even rarer. We report a case of parosteal lipoma of the rib in a young male with some unique features. This is the fifth case of its kind to be reported in literature.